Nanotubular polypyrrole: Reversibility of protonation/deprotonation cycles and long-term stability. (June 2019) - Prokeš, Jan; Varga, Martin; Vrňata, Martin; Valtera, Stanislav; Stejskal, Jaroslav; Kopecký, Dušan
Graphical abstract: Highlights: Alteration of conductivity by deprotonation/reprotonation is a reversible process. Deprotonation proceeds even at very low concentration of alkali. The absolute values of conductivity are given by the age of reprotonated samples. Deprotonation of polypyrrole nanotubes decreases the stability of conductivity. Universal relationship between ageing relaxation time and conductivity was found. Kinetics of degradation follows stretched-exponential function. Abstract: An alteration of electrical conductivity of the conducting polymers from a conducting to a non-conducting form and vice versa is a feature of the high importance. Here, the changes in conductivity of the polypyrrole nanotubes (PPy-NT) associated with a deprotonation/reprotonation in alkaline (various concentrations of ammonium or sodium hydroxide) or acidic (1 M hydrochloric or hydrobromic acid) solutions are presented. All experiments were followed by energy dispersive X-ray spectroscopy (EDX) elemental analyses and van der Pauw conductivity measurements. Extensive measurements of conductivity of samples during 2-years' timespan have also been made in order to determine the kinetics of natural ageing of the deprotonated/reprotonated PPy-NT. EDX measurements have allowed for a deeper insight into the process of the deprotonation/reprotonation of PPy-NT, which is generally characterized by the exchange of counter-ions and by the increase in the oxygen content. Correlations among conductivities of original, deprotonated and reprotonated samples revealed the universal behaviour, which can be used for the precise prediction of the ability of PPy-NT to be reprotonated by acids. Kinetics of the degradation of PPy-NT by natural ageing is faster for deprotonated sample and, on the contrary, the reprotonation by acids had a stabilizing effect.